THE FLIES OF THE GENUS HIPPELATES AS POSSIBLE VECTORS OF PINTO DISEASE - SOBERON, G; PARRA, GALO; LEON BLANCO, FRANCISCO (Laboratorio Experimental MicroBiología Natuaral ch Biología Sci, CD MEXICO, DF, MEX, 1946)
Serol differentiation between murine and classic typhus can be made by means of slide agglutinative tests The antigens are prepd from the lungs of mice inoculated by intranasal route Mixtures of the antigens and various dilutions of immune serum produ
CIENC MEX
Keywords: FLIES, GENUS, HIPPELATES, VECTORS, PINTO DISEASE; CIENCIAS MEDICAS; SALUD PUBLICA; ENFERMEDADES CONTAGIOSAS